HUBUNGAN TINGKAT KEMANDIRIAN DALAM AKTIVITAS SEHARI-HARI DENGAN RESIKO JATUH PADA LANSIA DI PSTW SABAI NAN ALUIH SICINCIN KABUPATEN PADANG PARIAMAN - Ulfa Suryani (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2018)
Fall is one of the most common physical problems in the elderly that results in morbidity and mortality in the elderly. One of the risk factors of fall is independence in daily activities. The purpose of this study is to know the relationship of independence level in daily activities with the risk of falling in the elderly at PSTW WerdhaSabai Nan AluihSicincin 2017.The design of this research was descriptive analytic with cross sectional approach. The techning sampling was Propotinal Simple Random Sampling with 52 samples. Data collection used primary with questionnaire Index Katz and morse fall scale .Univariate analysis is shown in frequency distribution and bivariate table by using chi-square test.The results showed that there was a relationship between the level of independence in daily activities with the risk of falling in the elderly in PSTW Sabai Nan AluihSicincin 2017 (p value = 0,019).Based on the results of this study the risk of falling related to the level of independence. Suggestions from this study are expected that the elderly who are at risk to fall can to reduce the independence in living daily activities in order to prevent the occurrence of falls.